Karakteristik Batubara Peringkat Rendah Formasi Bobong dan Implikasinya Terhadap Coal Liquefaction - Supardin Nompo; Bambang Sardi; Muhammad Arif (Jurnal Geomine, 2020)
This research was conducted on the Bobong Formation coal in the form of geochemical analysis. The Bobong Formation is geologically located in the Banggai Sula Basin, Pulau Taliabu Regency, North Maluku Province. The study focused on low rank coal on the liquefaction process. Sampling locations are carried out in each coal outcrop near the river channel north of Taliabu Island. Sampling is done by the ply by ply method. Sampling is done at several points of observation in the form of a station. Coal sample analysis is carried out in the form of proximate and ultimate. The coal liquefaction experiment through the pyrolysis method with assisted microwave was carried out with raw material in the form of 300 g of 20 mesh coal, 3 g active carbon catalyst, temperature of 600 C, vacuum pressure (-3 mmHg) and 600 watt microwave power. These problems are focused on the influence of low rank coal geochemistry of the Bobong Formation in the Banggai Sula Basin on coal liquefaction and the behavior of coal liquefaction on changes in time variables. The physical and chemical characteristics of coal in coal content are ash (16.36%) adb, inherent humidity (8.19%) adb, volatile substances (22.21)%) adb and fixed carbon (48.60% ) adb, hydrogen (4.55% adb), oxygen (25.94% adb), carbon (65.33% adb), sulfur (2.54% adb) and nitrogen (1.64% adb). The optimal coal liquefaction yield with a reaction time of 60 minutes is 49%. The results of coal liquefaction did not change at the reaction time of 70 minutes and 80 minutes, respectively 49.01% and 49.02%. Coal with more lignite is more easily liquefied than sub-bituminous because coal has a higher hydroxyl group.